PERSONAL GARANSI SEBAGAI JAMINAN PELUNASAN HUTANG DEBITUR KEPADA KREDITUR BEDASARKAN PUTUSAN NOMOR 173/PDT.SUS-PKPU/2019/PN NIAGA.JKT.PST - Putra, Dwi Yanri; Sucondro, Bambang (Fakultas Hukum Universitas Trisakti, 2023)
In credit agreements entered into by debtors with creditors, there is a principle of providing credit facilities by providing collateral other than material collateral, namely collateral guarantees, better known as personal guarantees, which means that there is a third party outside the credit agreement who guarantees that the debtor will fulfill all forms of obligations, namely to pay off